2012
DOI: 10.1016/j.pain.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Nav1.7-mediated pain in inherited erythromelalgia using a novel sodium channel blocker

Abstract: Mutations in the SCN9A gene leading to deficiency of its protein product, Na(v)1.7, cause congenital indifference to pain (CIP). CIP is characterized by the absence of the ability to sense pain associated with noxious stimuli. In contrast, the opposite phenotype to CIP, inherited erythromelalgia (IEM), is a disorder of spontaneous pain caused by missense mutations resulting in gain-of-function in Na(v)1.7 that promote neuronal hyperexcitability. The primary aim of this study was to demonstrate that Na(v)1.7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 16 publications
1
78
0
2
Order By: Relevance
“…Results from an oral Phase II study with XEN402 (16) suggested positive effects in patients suffering from primary erythromelalgia. 30 Xenon recently partnered XEN402 (TV-45070, 16) with Teva and have been granted orphan drug designation by the FDA for the treatment of erythromelalgia. Pfizer have advanced a Na V 1.7 compound PF-05089771 into Phase II clinical trials of third molar extraction and primary inherited erythromelalgia.…”
Section: Compounds In Clinical Development and Outlookmentioning
confidence: 99%
“…Results from an oral Phase II study with XEN402 (16) suggested positive effects in patients suffering from primary erythromelalgia. 30 Xenon recently partnered XEN402 (TV-45070, 16) with Teva and have been granted orphan drug designation by the FDA for the treatment of erythromelalgia. Pfizer have advanced a Na V 1.7 compound PF-05089771 into Phase II clinical trials of third molar extraction and primary inherited erythromelalgia.…”
Section: Compounds In Clinical Development and Outlookmentioning
confidence: 99%
“…A number of these compounds have now entered clinical trials for pain (Fig. 3), including the proline derivative 5 from GSK/Convergence, 11 a spiro-oxindole compound from Xenon (series exemplified by 6 XEN402, now known as TV-45070) 12 and an aminoheterocycle sulphonamide series from a Pfizer-Icagen collaboration (series exemplified by 7). 13 To-date, Xenon have reported efficacy treating pain in patients with congenital erythromelalgia, but no efficacy was seen in a study of postherpatic neuralgia.…”
Section: Ion Channel Modulators For Pain Therapy In Clinical Developmentmentioning
confidence: 99%
“…SCN9A mutations were found to produce different effects on the channel functions, which include enhanced activation (in PE) and impaired inactivation (in PEPD), giving some insight into the features of pain [46]. New compounds under development have been shown to engage Nav1.7 [50], suggesting that in the future, it will be possible to develop tailored treatments that target sodium channels.…”
Section: Sodium Channel-related Painful Neuropathiesmentioning
confidence: 99%